2008
DOI: 10.1038/cr.2008.287
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of RNAi by a small molecule antibiotic enoxacin

Abstract: RNAi has become a mainstream molecular tool for assessing the functions of genes in mammalian cells [1]. Large-scale RNA interference-based analyses are often complicated by false positive and negative hits due to off-target effects [2] and interferon response [3], which can be attributed at least in part to the use of high concentrations of siRNA. Lowering the amounts of siRNAs and shRNAs can effectively and expediently mitigate the off-target effect and interferon response [4]. However, in RNAi experiments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…To explore this, we assayed several fluoroquinolones for their ability to affect the interaction between V-ATPase and F-actin in vitro and to inhibit osteoclast formation. These included norfloxacin, which was reported to stimulate microRNA activity and others (pefloxacin and levofloxacin) that did not 19,21. We found that only pefloxacin had a detectable effect on the interaction between B-subunit and F-actin (Figure 7A).…”
Section: Resultsmentioning
confidence: 61%
“…To explore this, we assayed several fluoroquinolones for their ability to affect the interaction between V-ATPase and F-actin in vitro and to inhibit osteoclast formation. These included norfloxacin, which was reported to stimulate microRNA activity and others (pefloxacin and levofloxacin) that did not 19,21. We found that only pefloxacin had a detectable effect on the interaction between B-subunit and F-actin (Figure 7A).…”
Section: Resultsmentioning
confidence: 61%
“…Concurrent with our identification of enoxacin as an inhibitor of B2-microfilament binding, another group screening for small molecule modulators of microRNA activity identified enoxacin as a stimulator of microRNA processing, and suggested this was through interaction with TAR RNA-binding protein 2 (TRBP2) [108]. This finding could, in principle, explain some or all of the observations with regard to osteoclast formation and function.…”
Section: Introductionmentioning
confidence: 92%
“…We found that it could dramatically enhance the processing of shRNA into siRNAs and promote the loading of siRNAs/miRNAs into the RISC, significantly reducing the dosage required to achieve equal knockdown efficiency in mammalian cells (Shan et al, 2008). Enoxacin was identified as an RNAi enhancer in an independent chemical screening by another group, as well (Zhang et al, 2008). …”
Section: Dissecting the Mirna/rnai Pathway Using A Chemical Biology Amentioning
confidence: 99%